Firm Value Study Of Idx Bumn20 Companies In Indonesia - Rizal Syafiie, Moh.; Setiabudi, Acong; Huliawati, Riska (International Journal of Educational Research & Social Sciences, 2023)
The study was conducted because the phenomenon associated with IDX BUMN20 in the banking sector supports the index and is the top gainer. The aimed of this study is to examine the impact of financial performance on corporate value in the banking sector using the PER indicator (Price Earnings Ratio), mediated by the DER (Debt to Equity Ratio), and using the ROA indicator (Return on Assets). is to judge ratio). Listed in the IDX BUMN20 index. The object of this study is the banking sector listed on the Indonesian stock exchange IDX BUMN20. It has five sample companies analyzed for the period 2016-2021. This type of study uses a quantitative approach with purposive sampling techniques and WarpPLS 7.0. as a data analysis tool. The results showed that financial performance impacted enterprise value and DER (debt-to-equity ratio). On the other hand, the debt-toequity ratio has no impacted with enterprise value.